Aderência entre o aço e concreto fresco em condições de concretagem submetidas a vibrações - Belo, Gabryela Ferreira (2017)
Reinforced concrete structures require bond between steel and concrete to perform achieve functionality. This bonding occurs through the transfer of stresses from concrete to reinforcement. Repairs, rehabilitation and enlargement of bridges release for use using fresh concrete and placement of steel bars, cause vibrations that can modify the bond between steel and concrete. The main objective of this research was to evaluate the influence of the vibration signal type on the bond between steel and concrete when the fresh concrete is subjected to vibrations. Compressive strength was also evaluated because it is the main parameter for the construction criteria. The specimens used for the bond test consisted of 20 mm steel bars inserted into concrete specimens and the concrete compression strength (fck) was 20 MPa at 28 days, using the procedure described in RILEM RC-6 (1983). The samples were vibrated shortly after casting in an electrodynamic actuator simulating Peak Particle Velocity (PPV's) of bridges according to limits proposed in the literature and frequencies observed in brazilian bridges. The specimens were vibrated with two types of signal: sine and sweep sines with frequencies of 8.5 and 5-12 Hz, respectively. From the results it was possible to conclude that the vibrated concrete can have bond strength gains of up to 33.2% using the sweep sine with PPV of 5 cm/s. Opposite results were obtained from the compressive strength tests, which suffered reduction of up to 33% in their value using a sine signal with PPV of 5 cm/s.